A case of pulmonary mucosa-associated lymphoid tissue lymphoma diagnosed by detecting t(11;18)(q21;q21) in bronchial lavage fluid - Yusuke Nakamura; Akihiro Takemasa; Yuki Ohoka; Nobuhiko Tsukada; Azusa Tsukada; Yoshimasa Nakazato; Kinuko Mitani; Akihiko Toyoda; Yasuo Shimizu; Seiji Niho (Respiratory Medicine Case Reports, 2024)
A 76-year-old woman was diagnosed with mucosa-associated lymphoid tissue (MALT) lymphoma by upper gastrointestinal endoscopy. She underwent further investigation for concomitant bilateral pleural effusions and right pulmonary consolidation. MALT lymphoma with the t(11; 18)(q21; q21) translocation and API2-MALT1 were detected in pleural fluid. Lymphoma was not histopathologically diagnosed by lung biopsies, but the same translocation was identified in bronchial lavage. MALT lymphoma is often difficult to diagnose by bronchoscopy because of only mild dysplasia. However, present report on using chromosomal translocation analysis from bronchial lavage indicates that such testing may serve as a useful diagnostic adjunct in MALT lymphoma with lung involvement.